2017
DOI: 10.1016/j.radcr.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular paralabral cyst causing compression of the sciatic nerve

Abstract: Acetabular paralabral cysts are common. They vary in their clinical presentation and may be asymptomatic or cause pain and restriction at the hip joint. In rare instances they may cause symptoms by compressing local neurovascular structures. We report a case of symptomatic compression of the sciatic nerve by a posteriorly displaced acetabular paralabral cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…[ 6 ] A large paralabral cyst can cause compression of the femoral and sciatic nerves. [ 7 8 ] In this case, ultrasound-guided aspiration relived her discomfit and appeared to be a safe and effective procedure. However, the physicians are suggested to closely follow-up the patients because recurrence of the cystic lesion may happen after aspiration.…”
Section: Discussionmentioning
confidence: 82%
“…[ 6 ] A large paralabral cyst can cause compression of the femoral and sciatic nerves. [ 7 8 ] In this case, ultrasound-guided aspiration relived her discomfit and appeared to be a safe and effective procedure. However, the physicians are suggested to closely follow-up the patients because recurrence of the cystic lesion may happen after aspiration.…”
Section: Discussionmentioning
confidence: 82%
“…Minimally invasive aspiration of symptomatic paralabral cyst was described as a useful technique, [107][108][109] particularly in sports enthusiasts, and it is described in the subsequent section on intervention in sport.…”
Section: Hip Paralabral Cyst Aspirationmentioning
confidence: 99%
“…11). 107,108 Such cysts may be treated with aspiration and corticosteroid injection under real-time imaging guidance (►Fig. 12), 109 providing short-to intermediate-term relief.…”
Section: Groin and Hip Interventions In Athletesmentioning
confidence: 99%
“…Paralabral cysts can become large and compress adjacent structures including the sciatic nerve and the femoral neurovascular bundle. 5,6 However, there have been reports of labral cysts that do not correspond with the location of the labral tear. 7 The current article found that if cysts were in the anterosuperior or posterosuperior region of the acetabulum, then they were more likely to be associated with a labral tear.…”
mentioning
confidence: 99%
“…7 This case report described an ultrasound-guided cyst drainage, anterior labral repair, and posterior cyst decompression to treat the patient. [5][6][7] This kind of complex anatomic problem forces us think outside the box to comprehensively treat these rare patients that can present to us with symptoms that are not commonly seen in the young hip patient population.…”
mentioning
confidence: 99%